2020
DOI: 10.1161/hypertensionaha.120.14836
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Treatment for Black Adults With Apparent Treatment-Resistant Hypertension

Abstract: Resistant hypertension, defined as blood pressure levels above goal while taking ≥3 classes of antihypertensive medication or ≥4 classes regardless of blood pressure level, is associated with increased cardiovascular disease risk. The 2018 American Heart Association Scientific Statement on Resistant Hypertension recommends healthy lifestyle habits and thiazide-like diuretics and mineralocorticoid receptor antagonists for adults with resistant hypertension. The term apparent treatment-resistant hypertension (aT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, the restriction of dietary sodium intake by 1 g has shown a decrease in blood pressure by 2.1 mmHg, which would be beneficial in addition to the recommended therapy [12]. It is advised that blood pressure in TRH patients should be maintained at 130/80 mmHg or lower [13]. A study observed an increased utilization of ARBs, ACE inhibitors, CCBs, and thiazide-type diuretics in African American adults, ranging from 43.3% to 63.6% [13].…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the restriction of dietary sodium intake by 1 g has shown a decrease in blood pressure by 2.1 mmHg, which would be beneficial in addition to the recommended therapy [12]. It is advised that blood pressure in TRH patients should be maintained at 130/80 mmHg or lower [13]. A study observed an increased utilization of ARBs, ACE inhibitors, CCBs, and thiazide-type diuretics in African American adults, ranging from 43.3% to 63.6% [13].…”
Section: Managementmentioning
confidence: 99%
“…It is advised that blood pressure in TRH patients should be maintained at 130/80 mmHg or lower [13]. A study observed an increased utilization of ARBs, ACE inhibitors, CCBs, and thiazide-type diuretics in African American adults, ranging from 43.3% to 63.6% [13]. However, mineralocorticoids and diuretics of the thiazide-type are underutilized in African Americans despite their ability to lower blood pressure [13][14].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“… 45 Among Black individuals with resistant hypertension, only 5.9% were taking the recommended thiazide‐like diuretic, and only 9.8% were taking a mineralocorticoid receptor antagonist, which is the preferred 4th agent for resistant hypertension. 46 Interventions, such as behavioral economics (eg, defaults and nudges), 47 are needed to encourage providers to appropriately prescribe higher quality antihypertensive medication and to improve adherence.…”
Section: Next Steps To Make Progressmentioning
confidence: 99%